Stepping Into Danger: Risk Factors for Diabetic Foot Infections in Pakistan - Nazar, Shazia; Hina Abbas, Syeda; Shaheera Zaidi, Syeda; Sandeelo, Nabiya; Rahim Hingorjo, Mozaffer; Askari, Zainab (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: This study aimed to identify the patient-related risk factors for diabetic foot infections and assess their impact on disease progression. METHODOLOGY: A Cross-sectional study was conducted at Dow University Hospital, Karachi, from June to December 2023. A total of 150 diabetic patients were included using a non-probability purposive sampling technique. The inclusion criteria for this study consisted of diagnosed diabetic patients aged (57.11±9.83) years, with or without diabetic foot infections, who were willing to participate and provide consent. The exclusion criteria included non-diabetic individuals, patients with foot ulcers or infections unrelated to diabetes (e.g; trauma), those with incomplete clinical records or missing data, and individuals unwilling to participate. Data were collected using a self-designed questionnaire and clinical records, focusing on demographics, biochemical markers, and clinical factors such as peripheral neuropathy, peripheral arterial disease, osteomyelitis, and smoking history. Statistical analysis was performed using SPSS version 23. RESULTS: The study revealed that peripheral neuropathy (OR = 3.2), peripheral arterial disease (OR = 3.1), and smoking (OR = 2.0) were significant independent risk factors for diabetic foot infections. Infected patients also exhibited poor glycemic control, as evidenced by elevated HbA1c levels and an abnormal lipid profile characterized by higher LDL-c and lower HDL-c levels compared to the uninfected group. CONCLUSION: Peripheral neuropathy, Peripheral arterial disease, and smoking are major risk factors for diabetic foot infections.